CD38 Defines a Subset of B Cells in Rainbow Trout Kidney With High IgM Secreting Capacities - Martín, Diana; Perdiguero, Pedro; Morel, Esther; Soleto, Irene; Herranz-Jusdado, J. German; Ramón, Luis A.; Abós, Beatriz; Wang, Tiehui; Díaz-Rosales, Patricia; Tafalla, Carolina (Frontiers in Immunology, 2021)
CD38 is a multifunctional molecule that functions both as a transmembrane signaling receptor and as an ectoenzyme with important roles in cell adhesion, calcium regulation and signal transduction. Within the B cell linage, CD38 is expressed in diverse murine B cell subsets, with highest levels in innate B cell subpopulations such as marginal zone (MZ) B cells or B1 cells. In humans, however, CD38 is transiently expressed on early lymphocyte precursors, is lost on mature B cells and is consistently expressed on terminally differentiated plasma cells. In the present work, we have identified two homologues of mammalian CD38 in rainbow trout (Oncorhynchus mykiss), designating them as CD38A and CD38B. Although constitutively transcribed throughout different tissues in homeostasis, both CD38A and CD38B mRNA levels were significantly up-regulated in head kidney (HK) in response to a viral infection. In this organ, after the generation of a specific monoclonal antibody (mAb) against CD38A, the presence of CD38A+ populations among IgM+ B cells and IgM- leukocytes was investigated by flow cytometry. Interestingly, the percentage of IgM+CD38A+ B cells increased in response to an in vitro stimulation with inactivated Aeromonas salmonicida. Finally, we demonstrated that HK IgM+CD38A+ B cells had an increased IgM secreting capacity than that of cells lacking CD38A on the cell surface, also showing increased transcription levels of genes associated with B cell differentiation. This study strongly suggests a role for CD38 on the B cell differentiation process in teleosts, and provides us with novel tools to discern between B cell subsets in these species.